Factor that contribute towards the motivation of RISDA Melaka staff at workplace / Nadia Kaderi - Kaderi, Nadia (Faculty of Business and Management, 2010)
The purpose of this research is to find the motivators that motivate the RISDA Negeri Melaka staff at the workplace. The dependent variable is employees’ motivation and independent variables are wages, working conditions and job security. This research is being conducted at RISDA Negeri Melaka. In completing this research, about 70 questionnaires have been distributed to the respondents. The respondents are included all the staff in RISDA Negeri Melaka. In order to get the result for this result, the researcher has used SPSS program to analyze data from the information gathered. To analyze the data, the researcher has been used Reliability Analysis, Cross Tabulation Analysis, Frequency Distribution and Descriptive Statistic by using SPSS Program. Form the findings; the researcher indicates that the most of the respondents agree that job security is the most factors that motivate them at the workplace. Second is the wages and follow by the working condition that is the least factor that motivates the employee at the workplace.